Cerebriform cutaneous lesions in pemphigus vegetans - Meryl Sonia Rebello; Bhat M Ramesh; D Sukumar; Geethu F Alapatt (Wolters Kluwer Medknow Publications, 2016)
Pemphigus vegetans is an autoimmune bullous disorder characterized by vegetating lesions commonly over the flexures. A 42-year-old female patient came with pemphigus vegetans presenting with interesting cerebriform morphology of the cutaneous lesions over the flexures. Cerebriform tongue, a morphology with typical pattern of sulci and gyri over dorsum of the tongue is a well-known sign seen in pemphigus vegetans. Interestingly, we noticed the typical sulci and gyri pattern in the skin lesions of pemphigus vegetans over the flexures of the body. This clinical sign can be used as a clue in the diagnosis of pemphigus vegetans. Morphology and physical characteristics are important for the diagnosis of the disease. Clinical signs always give a clue to the probable or possible diagnosis in most of the dermatological conditions.